2013
DOI: 10.1371/journal.pone.0054940
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Developmental Timing, and Not Increased Levels of Experience-Dependent Neuronal Activity, Promote Barrel Expansion in the Primary Somatosensory Cortex of Rats Enucleated at Birth

Abstract: Birth-enucleated rodents display enlarged representations of whiskers (i.e., barrels of the posteromedial subfield) in the primary somatosensory cortex. Although the historical view maintains that barrel expansion is due to incremental increases in neuronal activity along the trigeminal pathway during postnatal development, recent evidence obtained in experimental models of intramodal plasticity challenges this view. Here, we re-evaluate the role of experience-dependent neuronal activity on barrel expansion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 106 publications
(124 reference statements)
6
18
0
Order By: Relevance
“…We found that the expansion of the PMBSF area and individual barrels in the adult embBE mouse is set during the first postnatal week, before the animal experiences any sensory input. These results are in line with recent observations in rodents enucleated at birth, where changes in gene expression and in the size of cortical areas were detected postnatally 23 44 . The fact that the enlargement of S1 and the reduction of A1 described in the MGv Kir mice are not correlated with a modification in the size of the respective thalamic nuclei supports a thalamo-cortical rather than a top-down 45 mechanism for plasticity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the expansion of the PMBSF area and individual barrels in the adult embBE mouse is set during the first postnatal week, before the animal experiences any sensory input. These results are in line with recent observations in rodents enucleated at birth, where changes in gene expression and in the size of cortical areas were detected postnatally 23 44 . The fact that the enlargement of S1 and the reduction of A1 described in the MGv Kir mice are not correlated with a modification in the size of the respective thalamic nuclei supports a thalamo-cortical rather than a top-down 45 mechanism for plasticity.…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, the plastic changes that occur in the cortex of sensory-deprived animals involve both the deprived and spared cortical areas. For example, removal of the eyes at birth leads to a reduction of the primary visual cortex and an expansion of the somatosensory cortical barrel-field in blind adult rodents 21 22 23 . Thus, there would appear to be some communication among distinct sensory systems and cortical areas, although the mechanisms that underlie such effects remain unexplored.…”
mentioning
confidence: 99%
“…These tactile inputs are processed in the BC, at layer IV of the somatosensory cortex (Petersen, 2007 ). We produced a chronic tactile deprivation by fulgurating the vibrissal follicles as previously described (Fetter-Pruneda et al, 2013 ) and used the expression of cytochrome oxidase to label the BC (Wong-Riley and Welt, 1980 ). At day 30 after WD, the expression of cytochrome oxidase was not observed in the BC, indicating that tactile inputs were permanently disrupted by our method.…”
Section: Discussionmentioning
confidence: 99%
“…These cross-modal alterations ultimately sharpen the tuning of barrel neurons in response to principal whisker stimulation (Jitsuki et al, 2011 ). Epigenetic changes, namely H4 deacetylation, are additional mechanisms that orchestrate the expansion of the barrel cortex following binocular enucleation in rats (Fetter-Pruneda et al, 2013 ). Together, these advances have led to subsequent whole cell recording experiments in juvenile mice with a different degree of visual deprivation (dark exposure, binocular enucleation and bilateral lid suturing) that confirmed distinct, independent functions and sensory requirements of unimodal vs. cross-modal synaptic plasticity.…”
Section: Cross-modal Plasticity: An Intriguing Response To Sensory Inmentioning
confidence: 99%